2015
DOI: 10.1371/journal.pone.0118961
|View full text |Cite
|
Sign up to set email alerts
|

Birth Prevalence of Neural Tube Defects and Orofacial Clefts in India: A Systematic Review and Meta-Analysis

Abstract: BackgroundIn the last two decades, India has witnessed a substantial decrease in infant mortality attributed to infectious disease and malnutrition. However, the mortality attributed to birth defects remains constant. Studies on the prevalence of birth defects such as neural tube defects and orofacial clefts in India have reported inconsistent results. Therefore, we conducted a systematic review of observational studies to document the birth prevalence of neural tube defects and orofacial clefts.MethodsA compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 22 publications
3
75
4
2
Order By: Relevance
“…The global average prevalence of all orofacial clefts is 9.92 per 10.000, but there is substantial variation among different population [18]. The higher birth defect prevalence rates were reported from East Asian and Native American populations followed by European and South Asian populations, while the lower birth defect prevalence rates were reported from African ancestry population [19][20][21]. In the current study, the incidence rates greatly vary within the different years (ranged from 2.1 per 1000 birth to 0.2 per 1000 birth).…”
Section: Discussionmentioning
confidence: 99%
“…The global average prevalence of all orofacial clefts is 9.92 per 10.000, but there is substantial variation among different population [18]. The higher birth defect prevalence rates were reported from East Asian and Native American populations followed by European and South Asian populations, while the lower birth defect prevalence rates were reported from African ancestry population [19][20][21]. In the current study, the incidence rates greatly vary within the different years (ranged from 2.1 per 1000 birth to 0.2 per 1000 birth).…”
Section: Discussionmentioning
confidence: 99%
“…Asia is more diverse than North America or Europe, since it includes some of the world's least developed as well as highly developed countries. The prevalence of NTDs in the countries in Asia varies considerably by geographical areas, with a reported prevalence between 0.2 and 58 per 1,000 births [11][12][13] . We have conducted a PubMed search for an actual prevalence of MMC in various parts of Asia.…”
Section: Actual Impact Of MMC In Asiamentioning
confidence: 99%
“…B12 reduce the incidence of neural tube defects and this is confirmed by prospective studies of NTD after supplementation of these vitamins. 1 Prevalence of neural tube defects are studied by various researchers. Moroccan study by Radouni confirmed that most common form of NTD is anencephaly (60%) and associated malformation is club foot (15% cases).…”
Section: However Nakatsu Et Al (2000) Observed 3 Sites Ofmentioning
confidence: 99%